Organizational Commitment as A Mediating Variable in the Correlation of Organizational Culture and Perceived Organizational Support With Organizational Citizenship Behavior - Gemintang, Raihan Akbar Cahya; Tubastuvi, Naelati; Suyoto , Suyoto; Widhiandono , Hengky (SENTRALISASI, 2026)
This study aimed to examine the effect of organizational culture and perceived organizational support on the Organizational Citizenship Behavior of educators (OCB) and staff at Muhammadiyah Islamic Boarding Schools in Banyumas Regency with organizational commitment as a mediator. This quantitative study collected primary data from questionnaires distributed via Google Form. The population of this study was 335 staff using a purposive sampling technique with a minimum work period of 1 year. The analytical tool utilized in this study is SEM-PLS 3. The R2 for Organizational Commitment is 0.851, and for OCB, it is 0.792. The findings revealed that organizational culture, perceived organizational support, and organizational commitment contributed a positive effect on Organizational Citizenship Behavior (OCB) with a path coefficient of 0.493, and the hypothesis was accepted, and organizational commitment could mediate the effect of organizational culture and perceived organizational support on Organizational Citizenship Behavior. Meanwhile, Organizational Culture did not demonstrate direct effect on Behavioral Citizenship Behavior.